Theoretical and applied approaches to the legal regulation of information security in the Republic of Belarus - Archakov, Vladimir Yu. (Journal of the Belarusian State University. Law, 2020)
The article substantiates the relevance of scientific research in the field of legal support of information security, the importance of a clear and complete understanding of its essence. Various points of view on the content of the concept of «information security» are revealed, the need for a comprehensive consideration in the humanitarian and technological aspects is argued. Based on national conceptual approaches to information security and existing practices, it is substantiated that in Belarus this concept lays the whole spectrum of relations inherent in the information sphere. At the same time, a fragmented study of the complex problems of its security entails the uncertainty of theoretical approaches and some shortcomings in legal support. The adoption of a comprehensive regulatory legal act regulating legal relations in the field of ensuring information security is proposed.